Implementation of Guidance and Counseling in Elementary Schools in Supporting Student Development Tasks - Prawita, Citra Bella; Firman, Firman; Neviyarni, Neviyarni; Amat, Muhammad Asyraf Bin Che (Widyagogik, 2023)
This study aims to find out how Guidance and Counseling is implemented in SD Negeri Percobaan and to find out the importance of Guidance and Counseling in elementary schools. The writing of this article uses a qualitative descriptive method. Data collection techniques in this study used interviews and documentation. The data analysis uses the Miles and Huberman models. From the discussion it can be concluded that the implementation of guidance and counseling in SD Negeri Percobaan is by integrating guidance and counseling material into the subjects. Guidance and counseling services need to be held in elementary schools so that the individual and all the potential possessed by students can develop optimally. Guidance and counseling in elementary school is carried out by the class teacher. Therefore the role of the classroom teacher in implementing counseling activities is very important in order to achieve the formulated learning objectives more effectively.